Sediment Characteristics of Iron Ore Waste on the Surface of Settling Ponds - K., Agus Prabowo; Gusty, Sri; Desy, Natsar (ASTONJADRO, 2025)
The Iron Ore Refining Industry in North Maluku, There is waste generated from the iron ore refining or extraction process that is deposited into a settling pond or shelter with a capacity of about 3 million cubic meters that is no longer in operation, This study describes the characteristics of iron ore waste sediments on the surface of the settling pond, with laboratory methods, namely testing physical properties based on SNI references for aggregate materials and identifying chemical compound elements with EDS. The physical characteristics of waste sediments have absorption of 3.20%, surface dry specific gravity of 3.11 gr/cc, sand equivalent of 94.4%, Modulus of Smoothness of 2.78 and Mud Content of 6.40% while for the content of chemical compounds contained in iron ore waste sediments based on the molar percentage of oxides, the highest is Iron oxide (FeO) of 70.08% then below that there is Silicon dioxide SiO2) of 18.29%.